Non-cognitive Values: A Warrant of the Rationality and Responsibility of Science - Lekka-Kowalik, Agnieszka (Ruch Filozoficzny, 2022)
Although the presence of cognitive values in science has been accepted for half a century, until recently it was claimed that the presence of non-cognitive values threatened the rationality and objectivity of science and it was a sign of a scientist’s weakness. This view appeared to be correct when cognitive and non-cognitive values were treated dichotomously, and science was seen as a set of theories and procedures. The analysis of science as a social practice shows however that this dichotomy cannot be maintained and that the scientist, when planning and conducting research, makes assumptions which include value judgments encompassing certain non-cognitive values. Ignoring the presence of non-cognitive values does not secure objectivity and rationality of science. On the contrary, since they are constitutive elements of scientific research, pretending that they do not work in research exposes science to ideologization. Rational subordination of science to them becomes a vehicle and a warrant of not only rationality but also objectivity and social responsibility of science. This in turn allows us to restore the proper place of science in culture.